The impact of needle exchange-based health services on emergency department use. - Pollack, Harold A; Khoshnood, Kaveh; Blankenship, Kim M; Altice, Frederick L (Journal of general internal medicine, 2002)
To examine the impact of the New Haven Community Health Care Van (CHCV), a mobile needle exchange-based health care delivery system, in reducing emergency department (ED) use among out-of-treatment injection drug users (IDUs) between January 1, 1996 and December 31, 1998.
Keywords: Connecticut; Emergency Service, Hospital; Female; HIV Infections; Humans; Male; Mobile Health Units; Needle-Exchange Programs; Substance Abuse, Intravenous; Time Factors